Hypoxia after stroke: a review of experimental and clinical evidence. (December 2016) - Ferdinand, Phillip; Roffe, Christine
Abstract Background Hypoxia is a common occurrence following stroke and associated with poor clinical and functional outcomes. Normal oxygen physiology is a finely controlled mechanism from the oxygenation of haemoglobin in the pulmonary capillaries to its dissociation and delivery in the tissues. In no organ is this process more important than the brain, which has a number of vascular adaptions to be able to cope with a certain threshold of hypoxia, beyond which further disruption of oxygen delivery potentially leads to devastating consequences. Hypoxia following stroke is common and is often attributed to pneumonia, aspiration and respiratory muscle dysfunction, with sleep apnoea syndromes, pulmonary embolism and cardiac failure being less common but important treatable causes. As well as treating the underlying cause, oxygen therapy is a vital element to correcting hypoxia, but excessive use can itself cause molecular and clinical harm. As cerebral vascular occlusion completely obliterates oxygen delivery to its target tissue, the use of supplemental oxygen, even when not hypoxic, would seem a reasonable solution to try and correct this deficit, but to date randomised clinical trials have not shown benefit. Conclusion Whilst evidence for the use of supplemental oxygen therapy is currently lacking, it is vital to rapidly identify and treat all causes of hypoxia in the acute stroke patient, as a failure to will lead to poorer clinical outcomes. The full results of a large randomised trial looking at the use of supplemental oxygen therapy are currently pending.